1989
DOI: 10.1037/0735-7044.103.2.356
|View full text |Cite
|
Sign up to set email alerts
|

Chronic voluntary nicotine drinking enhances nicotine palatability in rats.

Abstract: The response of rats to nicotine solutions was examined with the brief-exposure, taste reactivity test and a two-bottle, 24-hr preference test. In Experiment 1, naive nondeprived rats were administered intraoral infusions (0.8 ml infused during 1 min) of distilled water and 1 microgram/ml, 5 micrograms/ml, 10 micrograms/ml, 25 micrograms/ml, 50 micrograms/ml, and 100 micrograms/ml nicotine. The oral motor, taste reactivity (TR) responses of the rats were recorded during the infusion. Nicotine solutions up to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
34
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 21 publications
5
34
0
Order By: Relevance
“…Yet, present results do indicate that such a preference was highly stable during the whole 12-day-long experiment. In agreement with the considerations put forward by other authors (Zellman et al 1985;Flynn et al 1989), it seems likely that, following the first drinking sessions, the taste of nicotine became also associated with post-oral reinforcement. As a consequence, the preference for the drug solution and its taste did not vanish.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Yet, present results do indicate that such a preference was highly stable during the whole 12-day-long experiment. In agreement with the considerations put forward by other authors (Zellman et al 1985;Flynn et al 1989), it seems likely that, following the first drinking sessions, the taste of nicotine became also associated with post-oral reinforcement. As a consequence, the preference for the drug solution and its taste did not vanish.…”
Section: Discussionsupporting
confidence: 90%
“…At lower concentrations, the acute reaction to the taste of nicotine is reported to be "neutral." It has also been shown that, following a period of free-choice drinking between nicotine and water, a nicotine solution is able to elicit more ingestive responses than tap water, suggesting an increase in the immediate palatability of nicotine (Flynn et al 1989). From these results, authors have concluded that nicotine palatability is enhanced because of its pairing with positive post-oral reinforcement, a similar result being also evident with morphine solutions (Zellner et al 1985).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations